Shear behaviour of composite slab reinforced with steel fibre concrete topping - Sarbini, Noor Nabilah (2013)
The objective of this paper is to presents experimental results on the composite slab reinforced with steel fibre compared to prefabricated welded wire mesh in concrete topping; subjected to applied shear load. In order to achieve the objective, 24 composite slabs reinforced with different types and amounts of steel fibres were prepared. At the same time, three composite slabs reinforced with prefabricated welded wire mesh were also prepared as comparison. The type of steel fibres was hooked-end deformed with different dimension, which are; length of 50 mm with diameter of 0.75 mm and length of 33 mm with diameter of 0.55 mm. Both types of steel fibres were cast as concrete topping with amounts of 0.25, 0.50, 0.75 and 1.00 percents volume fraction to that of concrete volume. The result shows that by substituting prefabricated welded wire mesh with steel fibres improves the shear behaviour of the composite slab.